THE SOCIAL SCIENCES OF RELIGION IN BRAZIL - Sanchis, Pierre (Debates do NER, 2007)
This is a panorama of the successive meanings acquired by the Social Sciences of Religionduring their recent institutionalization in Brazil. Seven "moments" are emphasized, each with theirown respective density of thematic attention. The first of these moments comes from withinreligious institutions, a "religious sociology', that is gradually transformed and made autorxmous,becoming "Sodal Science of Religion". Afterwards, successive discoveries of popular religion weremade, being a politically impre gnat ed religion in a politically unstable society such as Brazil, witha persistent religious sense of religion, and whose questions sprang from secularization and theadvent of the New Religious Movements. Correlatively, what then called and still continues